2015
DOI: 10.1186/s40655-015-0005-5
|View full text |Cite
|
Sign up to set email alerts
|

A generalized syntactic schema for utterance particles in Chinese

Abstract: A novel analysis of the syntax of utterance particles in Chinese is proposed in this paper. In terms of their diachronic origin, there are two types of utterance particles in Chinese, namely predicative utterance particles and non-predicative utterance particles, both of which are derived by a generalized syntactic schema. It is proposed that utterance particles are the complement of a functional category, forming a conjunction structure. The schema can be applied to other sentence-final expressions in Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
(16 reference statements)
1
14
0
Order By: Relevance
“…Previous studies have shown that there is a correlation between SFPs and intonation (Zhang 2014;Tang 2015;Wakefield 2016). For instance, SFPs and some specific intonation are in complementary distribution.…”
Section: Mandarin Clause Type Anticipation and The Clausal Typing Mecmentioning
confidence: 94%
“…Previous studies have shown that there is a correlation between SFPs and intonation (Zhang 2014;Tang 2015;Wakefield 2016). For instance, SFPs and some specific intonation are in complementary distribution.…”
Section: Mandarin Clause Type Anticipation and The Clausal Typing Mecmentioning
confidence: 94%
“…The question particle "ne" at the end of the sentence does not carry any lexical meaning of interrogation; therefore it cannot be an interrogative head. This understanding of the syntactic behavior of particle as non-head also follows Kayne (2015) and Tang (2015). The wh-questions in the earliest found version of Tao Te Ching do not carry any question particles at the end of the sentences, and this also shows that question particles are not likely to be the heads of the sentence CP (Ma, 2017a).…”
Section: Null Spec Languagementioning
confidence: 81%
“…11 See Matthews and Yip (1994, chap. 18) and Tang (2015). then right in (3)/(5) is not a sentence-final particle in the usual sense of the term but rather an adjective akin to the adjective correct as in:…”
Section: Sentence-final Particlesmentioning
confidence: 99%